Tinjauan Umum Tentang Wali Nikah - Muhammad Lutfi Syarifuddin (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2018)
Judging from the root of the language, the word guardian comes from Arabic which means protector, guarantor (someone's life). While the word "guardianship" in Arabic is walayah (ÙˆÙ„Ø§ÙŠØ©). Whereas the word walayah is the masdar form of the verb ÙˆÙ„Ù‰ ÙŠÙ„Ù‰ ÙˆÙ„Ø§ÙŠØ© which means it is close to. Muhammad Abduh interpreted the verse that the man married himself and married the women who surrendered their affairs to other people (guardians). Because a woman cannot marry herself freely, but must be with a guardian. Because marriage is a renewal of relatives (family) and affection between families in association. It will not be perfect and the benefits will be achieved except with the help or intercession of the guardian as well as the existence of the woman's willingness and permission requirements frankly for the widow and in silence as a requirement for a girl who is still embarrassed. Islam is a general requirement of a guardian. Regarding the size of a religious guardian in Indonesia there are several opinions. First, besides being acknowledged by the person concerned, it was also recognized by the community, that he was indeed Islam. Second, whoever pronounces the two sentences of the creed and knows and believes in the truth - that is, there are no sayings and actions that are contrary to his confession. Fourth, looking at other than believes with the pillars of complete faith, they must also worship, especially praying and fasting